Sport Isn’t Sacred and Analytics Isn’t New: Challenging Common Notions About Sports Analytics - Grant Morgan; Marshall Magnusen (Journal of Applied Sports Management, 2022)
The authors add to the debate about whether sport and numbers can cohabitate in modern day athletics, three areas are explored (albeit briefly) in the present paper. The first area focuses on the newness (or lack thereof) of analytics. The second area focuses the objectivity of analytics. The third area focuses on the idea that athletic competition is somehow sacred and should not be soiled by applying various statistical methods to practical sport performance problems.
Keywords: sport analytics; sport management; analytics